Rehabilitation for people wearing offloading devices for diabetes‐related foot ulcers: a systematic review and meta‐analyses - K. Jones; M. R. Backhouse; J. Bruce (Journal of Foot and Ankle Research, 2023)
Abstract Background Offloading devices improve healing of diabetes‐related foot ulcers (DFUs) but they can limit mobilisation. Rehabilitation during or after removal of these devices may promote physical activity in a population at risk of poor health outcomes for which inactivity is a reversible risk factor. Methods This systematic review examined the effectiveness of rehabilitation interventions to promote physical activity during and/or after wearing an offloading device to treat diabetes‐related foot ulcers. Searches using MESH terms and free‐text combinations: ‘foot ulcer’, ‘diabetic foot’, ‘casts, surgical’, ‘orthotic devices' were applied to MEDLINE, Embase, The Cochrane Library and clinical trial registers for randomised and observational studies published to September 2022. Methodological quality assessment of included studies was undertaken using the Cochrane Risk of Bias (RoB 2.0) and Risk of Bias In Non‐randomised studies of Interventions (ROBINS‐I) tools. Results Of 3332 records identified, eight studies (441 participants), four clinical trials and four cohort studies, were included. None delivered or tested a structured rehabilitation programme, but all reported physical activity outcomes during or after device use. People wearing non‐removable total contact casts were less active than those wearing devices (SMD ‐0.45; 95% CI − 0.87 to − 0.04; p = 0.03; I2 56%; 4 trials). Diabetes‐related foot ulcers in people wearing total contact casts were more likely to heal compared to removable devices at 12 weeks (OR 2.69; 95% CI 0.97 to 7.45; p = 0.06; I2 = 64%; 4 trials) and 20 weeks (OR 2.35; 95% CI 0.95 to 5.82; p = 0.07; I2 = 65%; 4 trials). Conclusions Despite physical activity being low throughout off‐loading treatment, no studies have specifically tested rehabilitation. There is a need to investigate the clinical and cost‐effectiveness of rehabilitation programmes in this population. High quality trials are needed to provide robust evidence to support to rehabilitation after DFU treatment.